SOCIAL SUPPORT AS A PREDICTOR OF SOCIAL WELL-BEING AMONG FINE ARTS STUDENTS IN ENUGU STATE - Nebo, Romanus E. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Students' well-being has attracted considerable attention in the past few decades. The present study examined the variation in social well-being among fine arts students in Enugu state based on social support. Three hundred and twenty-seven students enrolled in three public tertiary institutions in Enugu State, Nigeria, participated in the study. The respondents were randomly pooled from the fine arts departments in the selected institutions. The respondents completed a self-report measure of the Social Well-being Scale, the Multidimensional Scale of Perceived Social Support (MSPSS). The regression model showed that social support statistically significantly predicted social well-being, F (1, 325) = 32.305, p < 0.05. Furthermore, the R2 indicated that the predictor variable contributed 24.9% of the variance in the social well-being of fine arts students in Enugu state. The study concludes that social support is an essential determinant of social well-being.